FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN BUCKET LATRINE PADA MASYARAKAT KELURAHAN BAGAN DELI KECAMATAN MEDAN BELAWAN TAHUN 2013 - fadhil munthe; taufik ashar; surya dharma (Lingkungan dan Kesehatan Kerja, 2014)
One of the health effort the society is preparing the facilities basic sanitation. Latrine healthy is an important part in preventing transmission of infection diseases originating from feces. For it, important to reck the factors associated with the use of latrines.This study aims to determine the factors associated with the utilization of latrine bucket at the Village Deli Sub Chart Medan Belawan in 2013.This type of research is a cross sectional analytic design. The population in this study were 393 families who have a latrine bucket with a sample of 100 respondents is by systematic sampling methods. Statistical test used was exact fisher test with confidence level p <0.05. This study aimed to determine the factors associated with the utilization of the bucket latrine in the Village Deli Sub Terrain Chart Belawan. The research method used is analytic cross sectional design. The sample was a family who has a latrine bucket of 100 respondents, results showed that the variables that have a relationship with the utilization of the bucket latrine is knowledge (P = 0.001), attitude (P = 0.012), education (P = 0.001), the condition of latrines (P = 0.001), water supply (P = 0.020) health (P = 0.001), and the role of community leaders (P = 0.001). Statistical analysis using exact fisher test. Conclusions of this study are all factors that have a relationship with the utilization of latrine bucket at the Village Deli Sub Chart Medan Belawan, namely knowledge, attitudes, education, latrine conditions, the role of health workers and the role of community leaders. It is therefore recommended need increased knowledge, improvement bucket latrine conditions, availability of clean water, as well as an increase in the role of health workers and community leaders in order to increase the utilization of latrine bucket. Keywords : Knowledge, Attitude, Bucket Latrine Conditions, Availability of Clean Water, Action of Paramedic, Action of Society, Waste Bucket Latrine.